Специфіка метатеоретичного підходу до дослідження матеріальних артефактів культури на різних наукових рівнях - Наконечна, О.В. (Культура народов Причерноморья, 2014)
У даній статті обґрунтовано специфічні особливості метатеоретичного підходу до
дослідження матеріальних артефактів культури. Проаналізована специфіка двох полярних типів
людського мислення – і техногенного міфологічного. Сформульовані основні постулати
метатеоретичного підходу в культурологічному дослідженні. Уточнено суб'єктно–об'єктні відносини у
сфері дослідження матеріальних артефактів як феноменів культури. Визначено різні наукові рівні
дослідження означеного предмета. В данной статье обоснованы специфические особенности метатеоретического подхода к
исследованию материальных артефактов культуры. Проанализирована специфика двух полярных типов
человеческого мышления – техногенного и мифологического. Сформулированы основные постулаты
метатеоретического подхода в культурологическом исследовании. Уточнены субъектно–объектные
отношения в сфере исследования материальных артефактов как феноменов культуры. Определены
различные научные уровни исследования обозначенного предмета. In this article considers specific features metatheoretical approach to the study of material culture
artifacts. Two polar types of human thought – is man–made and mythological – are specifics. Their comparative
analysis is conducted to determine the role and place of each type in the modern epistemological paradigm.
The metatheory as a methodological approach is specified. The basic postulates metatheoretical approach in the
study of material culture artifacts are formulated.
Subject–object relations in the sphere of research material artifacts as cultural phenomena are enunciated.
Several «levels of uniqueness» of the subject, arising at metatheoretical approach to research are identified.
Defined the different research levels of study indicated subject: metaphysical level allows you to explore
artifacts from the position of philosophy, cultural – as facts social and cultural reality, applied at the level of
their practical application.
It is proved that in modern science, the cultural level of the research artifacts mastered enough.